A14 Involving service users in prehospital emergency care through TRUST. Issue 11 (14th October 2011) - Evans, A; Snooks, H; Thomas, G; Porter, A; Gaze, S
Abstract : Background: Service user involvement in health and social care policy-making and research is increasingly encouraged to improve research quality, relevance and accountability. There are particular challenges when involving people in prehospital care research: it is a dynamic and urgent service delivery context; there are no obvious patient groups from which to recruit service users and anyone could be affected by an unplanned illness, accident or assault. TRUST (Thematic Research group for UnScheduled, emergency and Trauma care) is the only UK research network with an exclusive remit of research of emergency and unscheduled care. We wanted to involve service users in developing and undertaking research. Method: We recruited patients and carers through the Involving People network and Long Term Conditions Alliance Cymru. People with experience of emergency care or a condition at risk of requiring emergency care were included. We supported with information and expenses. Results: Service users are involved at four levels of TRUST activity. At least two people sit on TRUST's advisory group to consider strategic and operational issues. Service users attend research development groups. Examples include: involvement in a bid to evaluate an electronic patient record form; chronic conditions patients and carers research group; emergency care of stroke workshop. Service users join research management groups on funded TRUST-linked projects. TRUST supports researchers to sustain involvement, for example, SAFER (999 care for older people who fall) trials (1 & 2), PRISM (predictive risk stratification in primary care) evaluation. Service users are involved in data analysis and developing research papers (Patient experience study, chronic conditions policy evaluation). Discussion: Patients and carers have experience and knowledge relevant to developing and undertaking prehospital research. TRUST coordinates and supports service user involvement in research in this field. Service users have fed their views into meetings covering project-specific and strategic topics at all stages of the research process.